Pengaruh Etika Bisnis terhadap Loyalitas dan Kepercayaan Konsumen Pada Store Perfect 10 Beauty, Medan - Alia Oktavia; Afrizahanny Meivia; Daud Arifin; Fajar Maulana; Abdul Rahiem (Universitas Fajar, 2026)
This study aims to analyze the effect of business ethics on consumer trust and consumer loyalty at Store Perfect 10 Beauty, Medan. This research employs a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 80 respondents who had previously made purchases. The data analysis techniques include validity testing, reliability testing, multiple linear regression analysis, coefficient of determination (R²), and mediation testing using the Sobel test. The results show that business ethics has a positive and significant effect on both consumer trust and consumer loyalty. In addition, consumer trust also has a positive and significant effect on consumer loyalty. The mediation test results indicate that consumer trust is able to mediate the relationship between business ethics and consumer loyalty. The coefficient of determination (R²) value of 0.68 indicates that 68% of the variation in consumer loyalty can be explained by business ethics and consumer trust. This study concludes that the implementation of good business ethics can enhance consumer trust, which in turn leads to increased consumer loyalty. Therefore, companies are encouraged to consistently apply ethical business principles in order to build long-term relationships with consumers.